An insight into online shopping behaviour among young adults in Malaysia / Marziah Mokhtar ... [et al.] - Mokhtar, Marziah; Yusoff, Sabariah; Asmuni, Shahariah; M. Fauzi, Nur Ain (Universiti Teknologi Mara Selangor, 2020)
In twenty-first century, online shopping becomes increasingly popular as more people starts to shop online using their smart phones and internet. Online shopping is a process of buying and selling of products and services through internet. The purpose of this paper is to examine online shopping behaviour among young adults in Malaysia. This paper investigates four variables that influence young adults online shopping behaviour namely convenience, customers satisfaction, persived and price level. A survey has been conducted by distributing google form questionnaires through WhatsApps applications.The collected data was analised using both frequencies and multiple regression analyses. The empirical findings of this study shows that convenience, customers satisfaction and price level positively influence the online shopping behaviour among adults. In contrast, persived risk has a negative effect with regards to online shopping. Among the four variables, convenience, persived risk and price level were found to be significant while consumer satisfaction was not.